A new species and new records of dung-associated bolbitiaceous fungi (Bolbitiaceae, Basidiomycota) from Uruguay - Morera, Guillermo; Kuhar, Francisco; Rodriguez, Luisina; Carrera, Ignacio; Davyt, Danilo; Rizzo, Sandra Lupo (Phytotaxa, 2024)
Coprophilous basidiomycetous fungi constitute a distinct ecological group, essential for the recycling of cellulose and other polymers digested by herbivores, and exhibiting adaptations such as thick-walled basidiospores. The family Bolbitiaceae, including the genera Pholiotina, Conocybe and Bolbitius, is well-represented on animal dung. Nonetheless, the coprophilous fungal diversity of Uruguay remains largely unexplored. This study aims to expand the knowledge of Uruguayan coprophilous fungi through the analysis of basidiomes collected from horse and cow dung samples, and using morphological, chemical and multilocus phylogenetic analyses (including ITS, LSU and Tef1-α regions). We recorded and characterized Pholiotina coprophila and Conocybe rufostipes for the first time in Uruguay and also identified and described a new species: Conocybe pruinosa sp. nov. Based on previous reports for related species, we searched for psychoactive tryptamines, but none of the samples in this study showed detectable concentrations of psilocybin or psilocin. Interestingly, in all cases, the clades consisted of sequences from Asia, Europe, North America and now Uruguay, which may correlate with the introduction of bovine cattle from these regions into the country.